A Review on Structural Performance of Bamboo Reinforced Concrete - Solahuddin, B. A. (Trans Tech Publications Ltd, Switzerland, 2022)
The technique of using small diameter whole-culm and split bamboo has been often suggested as an alternative method for concrete strengthening. Bamboo is widely available in tropical and sub-tropical locations, while the quest for a new sustainable alternative is a new and recent trend in the construction industry. Using bamboo in reinforced concrete is discussed in this paper and it is analysed as a structural and environmental alternative to steel reinforced concrete. Reinforced concrete is widely used in many countries where bamboo reinforced concrete might be used as a design alternative to determine the life cycle of reinforced concrete. However, bamboo was extraordinary material. Therefore, it is used in reinforced concrete due to significant durability and reduced stiffness problem, which positively impacts the environment. Hence, this paper discusses a review on the structural performance of bamboo reinforced concrete based on previous research.